Pengaruh Model Problem Based Learning berbantuan Resitasi terhadap Kemampuan Berpikir Kreatif kelas XI SMAN 6 Pekanbaru - Pujiati TM, Indah; L, Mariani Natalina; Putra, Riki Apriyandi (Jurnal Penelitian Pendidikan IPA, 2024)
The aim of this research is to determine the effect of the recitation-assisted problem based learning model on the creative thinking abilities of class XI SMAN 6 Pekanbaru. The research was conducted in April-June 2023 class XI SMAN 6 Pekanbaru. The research uses a quasi-experimental type of pretest-posttest control design. Sampling using random sampling, obtained an experimental class at XI MIPA 4 and a control class at XI MIPA 6, namely 72 students. The data collection technique used was creative thinking test questions. The pretest research results for the control and experimental classes were 34.94 categorized as very less creative and 37.69 categorized as very less creative, and the posttest for the control and experimental classes was 68.22 categorized as quite creative and 77.72 categorized as creative. Parameters using the pretest normality test sig 0.061 and posttest 0.15 are normally distributed. The homogeneity test obtained by the pretest was sig 0.89 and the posttest was 0.67 meaning it was homogeneous. Hypothesis testing obtained sig 0.00 < 0.05, H1 was accepted. This shows that the problem based learning model assisted by recitation has a significant effect on the creative thinking ability of class XI SMAN 6 Pekanbaru.